Psychological Content and Dynamics of Learning Activity Goals in Students of Pedagogical University - Yu.N. Slepko (Moscow State University of Psychology and Education, 2022)
The paper presents materials of a comparative empirical study of the developmental features of learning activity goals in students of pedagogical university. The materials were obtained on a sample of 1-4-year students, future primary school teachers. The work was aimed at identifying the abovementioned features as well as their relationship with motivation and successful training. The sample (N=118) included respondents aged 17 to 22 (M=19.5; SD=1.24), 99% of whom were female: 1st-year students N=42 aged 18 to 19 (M=18.1; SD=0.41); 2nd-year students -N=24 aged 18 to 20 (M=19.3; SD=0.56), 3rd-year students N=27 aged 19 to 21 (M=20.1; SD=0.58); 4th-year students N=25 aged 20 to 22 (M=21.0; SD=0.61). Empirical methods were used to assess the significance and content of the goals of learning activity (Questionnaire "Learning activity goals") and learning motivation ("Technique for assessing learning motivation and emotional attitude to learning" by A.M. Prikhozhan). Training success was evaluated basing on the indicators of academic performance in students. The results obtained reveal that over the course of training there is a gradual decrease in the significance of academic performance and an increase in the significance of self-development goals, diffuse goals. Comparative analysis of groups of students with varying degrees of training goals significance showed growing differences in emotional experience and anxiety in relation to educational outcomes. A moderate negative relationship was found between the significance of training outcomes and academic performance in students. This confirms the contradiction between the assessed academic performance and students' notions about the content of their future pedagogical activity.